Morphological typology : from word to paradigm - Stump, Gregory T. (Gregory Thomas), 1954-; Finkel, Raphael A. (Cambridge studies in linguistics ;, 2013)
This radically new approach to morphological typology is designed to engage graduate students and academic researchers.